2012
DOI: 10.1371/journal.pone.0042223
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Subtype F1 Epidemiological Networks among Italian Heterosexual Males Are Associated with Introduction Events from South America

Abstract: About 40% of the Italian HIV-1 epidemic due to non-B variants is sustained by F1 clade, which circulates at high prevalence in South America and Eastern Europe. Aim of this study was to define clade F1 origin, population dynamics and epidemiological networks through phylogenetic approaches. We analyzed pol sequences of 343 patients carrying F1 subtype stored in the ARCA database from 1998 to 2009. Citizenship of patients was as follows: 72.6% Italians, 9.3% South Americans and 7.3% Rumanians. Heterosexuals, Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
3
11
1
Order By: Relevance
“…Our results regarding C and F1 variants are in agreement with previous Italian data indicating a high relation between the South American strains, and those circulating in Italians and further showed that B subtype was imported from Latin American countries 27 28. Uncertainty cannot be completely avoided, as these individuals frequently travel abroad, and we cannot rule out transmission events in other countries during their permanence in Italy.…”
Section: Discussionsupporting
confidence: 91%
“…Our results regarding C and F1 variants are in agreement with previous Italian data indicating a high relation between the South American strains, and those circulating in Italians and further showed that B subtype was imported from Latin American countries 27 28. Uncertainty cannot be completely avoided, as these individuals frequently travel abroad, and we cannot rule out transmission events in other countries during their permanence in Italy.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis provided has the purpose to represent the evolution within a cluster of people with a strong association of predisposing and geographical factors and therefore determine relationship into the sources of an epidemic of ongoing viral spread, at the level of the population. Another large cluster was identified in F1 subtype, with 10 heterosexual Italian individuals, a finding which had already been reported for this subtype [18].…”
Section: Discussionsupporting
confidence: 73%
“…Also, in Italy, a B subtype prevalent area, some different geographically restricted non-B subtypes and CRFs are now penetrating, favored by immigration and travels [18][19][20][21]. A recent study has shown, in fact, an increase of non-B variants from 15.8% to 29.7% during the study period [22].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, despite the reported decrease of infections due to injecting drug usage ( http://www.iss.it/binary/ccoa/cont/ONLINE_6_COA_2014.pdf ), the circulation of A1 subtype partially remains related to this modality of infection as in previously documented A1 epidemics of East European countries [ 21 ]. In contrast with previous published data regarding other non-B subtypes circulating in Italy, such as subtype C and F1 which mobility is associated with men having sex with men, the A1 subtype remains related to heterosexuals and IDUs [ 25 , 26 ].…”
Section: Discussioncontrasting
confidence: 67%